A Quantum Chemical Descriptor for CVD Precursor Design: Predicting Decomposition Rates of TBP and TBAs Isomers and Derivatives1. Issue 7 (September 2015) - Stegmüller, Andreas; Tonner, Ralf
Abstract : Easily accessible information from quantum chemical computations can be used to predict decomposition barriers for phosphorous and arsenic precursor molecules for CVD. Based on the mechanistic description of the β ‐hydrogen elimination reaction, a precursor with a very low decomposition barrier is suggested.